2022
DOI: 10.52380/ijpes.2022.9.1.744
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Xenophobia Scale to Turkish: A Validity and Reliability Study

Abstract: In this research, we aimed to adapt the Xenophobia Scale developed by Olonisakin and Adebayo (2021) into Turkish. We conducted research on two separate study groups comprising 563 teacher candidates. Before starting the adaptation process of the scale, we obtained necessary permissions from the authors, who developed the original form. When developing the translation form, we removed two of the scale items from the instrument because they were not suitable for the Turkish culture. Afterwards, we performed an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For example, Beghetto (2009) examined intellectual risk-taking as a science-focused, and İlhan and Çetin (2013) focused on mathematics. On the other hand, Gezer et al (2014) examined intellectual risk-taking behavior with a focus on social studies and revealed that intellectual risk-taking behavior generated a conflict between approach (hope of success) and avoidance (fear of failure) tendency. They explained the tendency to stay away from the target due to fear of failure as avoiding taking intellectual risk, and the tendency to accept the possible risks related to the target and take action despite these risks as approaching intellectual risk-taking (Gezer et al, 2014).…”
Section: Intellectual Risk-taking In Social Studies Coursementioning
confidence: 99%
See 2 more Smart Citations
“…For example, Beghetto (2009) examined intellectual risk-taking as a science-focused, and İlhan and Çetin (2013) focused on mathematics. On the other hand, Gezer et al (2014) examined intellectual risk-taking behavior with a focus on social studies and revealed that intellectual risk-taking behavior generated a conflict between approach (hope of success) and avoidance (fear of failure) tendency. They explained the tendency to stay away from the target due to fear of failure as avoiding taking intellectual risk, and the tendency to accept the possible risks related to the target and take action despite these risks as approaching intellectual risk-taking (Gezer et al, 2014).…”
Section: Intellectual Risk-taking In Social Studies Coursementioning
confidence: 99%
“…On the other hand, Gezer et al (2014) examined intellectual risk-taking behavior with a focus on social studies and revealed that intellectual risk-taking behavior generated a conflict between approach (hope of success) and avoidance (fear of failure) tendency. They explained the tendency to stay away from the target due to fear of failure as avoiding taking intellectual risk, and the tendency to accept the possible risks related to the target and take action despite these risks as approaching intellectual risk-taking (Gezer et al, 2014). Pupils with an advanced disposition to avoiding academic risk have low achievement motivation and these students choose learning tasks according to the difficulty level of the task; namely, since they think that they can perform easy learning tasks with a little effort, they tend to take risks in the face of such tasks.…”
Section: Intellectual Risk-taking In Social Studies Coursementioning
confidence: 99%
See 1 more Smart Citation